Uso de Cianoacrilato en la Síntesis de Colgajos Mucoperiosticos. Comparación con el uso de Sutura de Seda - Pineda Mejia, Martha Elena (2003)
The tissue adhesive based on cyanoacrylate monomers created by their investigators for the synthesis of recent surgical or traumatic wounds, has had a really extensive use in skin wounds treatment. In this investigation the cyanoacrylate is evaluated in the synthesis of mucoperiostal flaps in the buccal cavity comparing with the use of conventional silk suture 3/0. For this reason 20 patients of the Central Clinic Surgery Service of our Dentistry Faculty, who were going to have a surgical intervention for the extraction of impacted teeth, were selected, the mucoperiostal flaps synthesis were made using both methods. From the wound healing evolution observation in a period of 14 days we reached the following conclusions: 1) the use of butyl cyanoacrylate as a mean of confrontation of mucoperiostal flaps basically diminished the operative time of placement, virtually painless method since puncture was not used in its placement, it didn’t need to be removed, it protected the wound of the bacterial plaque deposit, it diminished at maximum the presence of signs around the wound healing like bled, infection, edema and overalls erythema, in the observation time of the study. 2) The use of conventional suture allowed a scaring process that although it showed discreet bacterial plaque presence on the threads, light bled and cases of erythema in the puncture areas, however cases of dehiscence were not presented as it did happen with cyanoacrylate. The conformity expressed by the patients that used cyanoacrylate allows us to recommend this material for adults as well as for the surgical treatment in children.